The performance of lightweight concrete incorporating various percentages of SLAG and PFA [compact disc] - 203520 Ng, Pooi Yen (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005